Paper-based membranes on silicone floaters for efficient and fast solar-driven interfacial evaporation under one sun. Issue 31 (24th May 2017) - Wang, Zizhao; Ye, Qinxian; Liang, Xingbo; Xu, Jiale; Chang, Chao; Song, Chengyi; Shang, Wen; Wu, Jianbo; Tao, Peng; Deng, Tao
Abstract : A paper-based reduced graphene oxide composite membrane is integrated with a floating silicone-based thermal insulation layer for high-efficiency, fast-response solar-driven interfacial evaporation under one-sun illumination. Abstract : Solar-driven water evaporation has emerged as a highly efficient solar-thermal process to harness abundant clean solar energy for a variety of important applications. Herein, we rationally designed and developed a high-efficiency and fast-response solar-driven interfacial evaporation system by integrating a paper-based reduced graphene oxide (PrGO) composite membrane on top of a silicone-based porous insulation layer (PIL). The PrGO membrane that was prepared by using a cost-effective, scalable, simple fabrication process could effectively absorb and convert broadband solar light into heat to drive the evaporation process. Simultaneously, the hydrophilic PrGO membrane could provide continuous water supply through its strong capillary wicking effect. The floating PIL not only physically suspends the PrGO membrane but also thermally localizes solar heating at the air–water interface by suppressing downward heat conduction loss. Under one-sun illumination for 30 min, the resultant PrGO-PIL solar-driven interfacial evaporation system achieved steady-state and time-averaged evaporation efficiency of 89.7% and 80.6%, respectively. Theoretical analysis indicates that advantageous thermophysical properties of the evaporating materials together with rational design of the evaporation structure contribute to the superior evaporation performance. Such a high-efficiency solar-driven interfacial evaporation system has enabled consistent high-performance solar desalination of seawater under ambient one-sun illumination.